Dekolonisasi dan Indegenisasi Ilmu Pemerintahan - Andi Luhur; Abdillah Abdillah (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2020)
The post-colonialism syndrome is very difficult to remove in developing countries. Almost all areas of life are still connected with colonialization practices, including the development of science. The development of modernity and globalization in the third world has increasingly marginalized lokal social science theories. The development of science is not sufficient to explain the direction of global development and answer lokal problems, academically and practically. As in the use of the concept of government science from the perspective of bestuurskunde, American politics, and good governance is such formula of western civilization, which is transmitted in the form of academic colonialism. The existence of government science academically and practically is important to transform lokal wisdom models into new perspectives. Scientific wisdom as a source of inspiration for government science academically and practically must be decolonialization and indigenization in answering governance problems. The research method is descriptive qualitative with a decolonialization approach. Data processing techniques through pragmatic dialectics, by formulating new scientific syntheses. The results of this study emphasize that the science of government as knowledge of liberation must be transformed from a spirit of liberation (decolonialization) to a scientific discourse typical of Indonesian lokal wisdom (indigenization). Indonesian lokal wisdoms such as the concept of Wanua in Soppeng, South Sulawesi, and the Civil Service of the Javanese Bureaucracy, Bugis-Makassar Political Culture, to the policy model of the Islamic Mataram Kingdom are the scientific manifestations of Indonesian government as a treasure trove of scientific wisdom. The strategy of decolonialization and indigenization of government science is needed to explain governance problems that cannot be explained by other scholars. Because the science of government is not just to improve the skills of government officials or to inspire government service practices, but also to build political and bureaucratic traditions based on their social reality.